Assessment of clinically relevant dose distributions in pelvic IOERT using Gafchromic EBT3 films. Issue 7 (November 2015) - Costa, Filipa; Sarmento, Sandra; Sousa, Olga
Abstract: Purpose: In IOERT a single dose of radiation is delivered to the tumour site during surgery. Manual dose calculations are used and the irradiation target volume, electron energy and applicator are decided on site by the radiation oncologist. This work assesses the effect that irregular and curved surfaces, typical of pelvic IOERT, may have on the expected dose distribution. Methods: The feasibility of using Gafchromic EBT3 films and a slab phantom to obtain 2D dose distributions was investigated. Different set-ups were tested by comparison with water tank measurements, applying the gamma function analysis with 2% and 2 mm criteria. The validated set-up was then used to obtain reference dose distributions, which were converted to colour-coded graphical representations. Phantoms with step-like and curved surfaces were created to simulate typical pelvic IOERT irradiation surfaces, and the dose distributions were obtained and compared with the reference distributions. Results: Good agreement with water tank measurements was obtained for all applicators below 2 mm, using the chosen setup in reference conditions. In non-reference conditions, the presence of a step-like surface creates an adjacent hotspot, followed by a quick reduction of the dose in depth. With curved surfaces, the dose distribution is shifted forward, becoming curved and deeper, but when the applicator is larger than the hole, hotspots are also observed. Conclusions: The shape of the irradiation surfaces alters the dose distribution. Visualization of these effects is important to assess target coverage and interpret in vivo measurements in pelvic IOERT. Highlights: Curved and/or irregular irradiation surfaces are frequently used in pelvic IOERT. Our results show that irregular surfaces change the expected dose distribution. Tissue partially covering the applicator opening creates adjacent hotspots. Visualization and interpretation of these effects is needed for radiation oncologists. Films and slab phantoms, if properly handled, are a good way to obtain 2D dose distributions in IOERT.